Review of Government Regulation No. 50 Of 2012 and Maqashid Shariah on the Occupational Health and Safety Management System at PT. Industrial Chemitomo Nusantara - Alfarishi, Ari Dezan; Mustafa, Muhammad Isa (INSTITUT AGAMA ISLAM TAZKIA, 2022)
The purpose of this study is to analyze whether OHSMS pt. Industrial chemitomo nusantara is in accordance with government regulation number 50 of 2012 and analyzes whether OHSMS is pt. Industrial chemitomo nusantara has maqashid sharia value in it. This research uses a qualitative method with a research approach using case studies, where case studies are a comprehensive explanation of various aspects of an individual, a group, organization, program, social situation and with this approach can be used to analyze policies and regulations. Data collection is carried out by means of observation, interviews and documentation. The results of this study show the findings that, the OHS Management System in PT. Industrial Chemitomo Nusantara is in great accordance with Government Regulations in terms of OHS policy, OHS planning, OHS planning implementation, monitoring and evaluation of OHS performance as well as reviewing and improving OHS performance. In addition, OHSMS has a maqashid value in it.